HADIS DA’IF DAN MAWDU’ DALAM KITAB NASA’IH AL-‘IBAD OLEH NAWAWI BANTEN : ANALISA TERHADAP KONTEN HADIS - Arwansyah Kirin; Siti Marpuah; Muhammad Masruri (Al-Amien Prenduan for Islamic Institute, 2021)
AbstractThe book of Nasa'ih al-Ibad by sheikh Nawawi al-Banteni is a classic book containing aspects of Targhib wa Tarhib, which is widely distributed in Southeast Asia, especially in Indonesia and it is widely used in pesantran and pondok today. Sheikh Nawawi al-Banteni refers much to the Prophet's hadiths as a main sources and evidences to argument that he mentions in her book. The problem with this book contains unknown status of hadith and which are became a daily reference and practice for the Muslim community. This study is very important to understand the ruling of practice with the Hadith Da'if and Mawdu’ for the Muslim community in Southeast Asia. The objective of this study is to analyses the status of hadith in chapter 5-10 either as sources of ruling. The methodology used is content analysis from the Nasa'ih al-'Ibad book, while analyzing the study data using inductive methods. Based on analysis done on chapter 5-10 in the book, only 23.0% of hadith can be used in Fada'il al-Amal, when it has met certain requirements set by scholars. Therefore, this thematic analysis is importance to ensure the percentage Hadith Da'if and Mawdu and the ruling of hadith Da’if can be practiced is only for Fada’il al-‘Amal. The status of hadith is importance to Muslim as second sources of Islam.